Eighteenth-century responses to Sophocles' Oedipus at Colonus - Ryan, Cressida (2010)
This thesis is a synchronic reception study of a single play, the Oedipus at Colonus. Rather than providing a commentary, or extracting one or two themes in isolation for examination, it considers the play through the lens of the eighteenth century. In so doing it offers a variety of disciplinary approaches, looking at the QC through the eyes of an aesthetic philosopher, creative writer, textual critic, artist, politician, historian, art historian, composer, musicologist, teacher or clergyman. After an introduction outlining some basic presuppositions for the thesis, chapter 1 covers aesthetic philosophy, chapter 2 books, chapter 3 staged reworking, chapter 4 paintings and chapter 5 opera. In reflecting on the play from such a broad range of perspectives, a range of insights emerge. The major theme is the way in which aesthetics develops over time and how these developments are reflected in the wide range of material under discussion. This thesis is about the sublime. Reading the DC through eighteenth-century eyes prioritises certain aspects of it which can, in various guises and at various times, be understood as sublime. This places great emphasis on themes such as religion and the role of landscape, while diminishing others, such as that of blindness, which might usually seem obvious ways to think about the play. Each act of reception draws out something slightly different from the Greek model, and by examining a range of material, our overall appreciation of the play and the eighteenth century is significantly enhanced, particularly in respect to the aforementioned themes.